Sustainability transitions in urban basic infrastructure services: Organising principles from Southern cities - Oates, Lucy (A+BE | Architecture and the Built Environment, 2025)
Urban infrastructure and the essential services it provides – energy, housing, transport, waste management, and water – are fundamental for human and ecological wellbeing. As urban populations grow, particularly in the Global South, equitable and sustainable service delivery is increasingly identified as a strategy for addressing both environmental and socioeconomic development challenges. Existing frameworks for sustainability transitions often prioritise technological innovation at the expense of social, political, and organisational dimensions of infrastructure. Likewise, mainstream approaches to infrastructure development favour large-scale, centralised, technology-driven solutions, overlooking the diverse service delivery arrangements that characterise many Southern cities. This thesis addresses this gap, combining empirical case studies with critical discourse analysis to explore how community-led and hybrid service delivery models contribute to inclusive and sustainable urban development. First, it examines how academic and policy discourses reveal a bias towards technocentric, Global North-focused perspectives on sustainable infrastructure. Next, it draws on case studies from 14 cities from across Africa, Asia, and Latin America to explore the delivery of essential services by community-based organisations, cooperatives, and informal service providers. Often considered “unorthodox,” such models can – given appropriate state support – contribute to improving service accessibility, mitigating environmental impacts, and empowering marginalised communities. Finally, these findings are used to propose refinements to sustainability transitions theory, including the Multi-Level Perspective. The thesis concludes that policy, practice, and academic theory must shift away from a narrow emphasis on technological solutions or economic efficiency, embracing broader approaches to urban service delivery that can benefit both human wellbeing and environmental sustainability in cities worldwide.